Management of sternebral osteomyelitis in a horse - Rhoads, W. S.; Neuwirth, L.; Gull, T.; Pack, L. A. (Veterinary and Comparative Orthopaedics and Traumatology, 2001)
Sternal osteomyelitis should be considered as a differential diagnosis for horses with chronic swelling and drainage from the ventral thorax. Other differentials should include foreign body, fungal infection or neoplasia. The sternum can become infected from direct trauma or penetrating wounds, or secondary to extension of a distant site of infection, including septic jugular thrombophlebitis. Radiographs can be obtained of the caudal sternum in the standing horse. Partial sternebrectomy can be effective for the treatment of sternal infections in horses.Sternebral osteomyelitis is uncommon in animals. The case reported describes the pathogenesis and treatment of sternebral osteomyelitis that developed in a horse following abdominal surgery. Partial sternebrectomy, local, and systemic antimicrobial therapy were effective in resolving the infection and returning the horse to its previous use.
Keywords: Horse; sternum; osteomyelitis; sternebrectomy